Only by faith (religious reformist views by Francysk Skaryna) - Orgish, Viachaslau P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
There are some aspects in Modern Studies on Francysk Skaryna that are the subject to reconstruction and new interpretation. Among them we can note the activity of Francysk Skaryna as a translator, an interpreter, and a publisher of the biblical texts that became a necessary precondition and intellectual anticipation of the Belarusian Reformation. The dominant view of the researchers on the Renaissance-humanistic aspect of his worldview can narrow down the understanding of his cultural and historical mission. The analysis of Skaryna’s outlook suggests a well-known parallelism, closeness and in some cases a convergence with the ideas of the German reformer Martin Luther. Skaryna was the first one among Belarusian intellectuals and cultural figures who began to interpret Christianity from an unorthodox point of view. In Belarus it was him who started to interpret the Christianity through the prism of Reformation. Based on F. Skaryna’s Introductions and Epilogues to Biblical books this article reveals his religious and reformist views.